Scientific computing and cultural heritage: contributions in computational humanities - Bock, Hans Georg; Jäger, Willi; Winckler, Michael J. (Contributions in mathematical and computational sciences, 2013)
I. Development of Scientific Computing Methods -- II. Information-Based Research -- III. Case Studies & Applications.
Description based upon print version of record
Keywords: Aufsatzsammlung; Visualisierung; Informationssystem; Digitalisierung; Kulturerbe